Campaign financing and candidate profiles in 2020: Indonesian insights for the 2024 Regional Election - Dewi Sadtyaji; Teguh Yuwono; Yuwanto Yuwanto; Nunik Retno Herawati (Komisi Pemberantasan Korupsi, 2025)
This study examines campaign financing and candidate profiles in the 2020 Indonesian regional election, offering insights for the 2024 race. Employing a mixed methods approach with quantitative surveys and qualitative interviews, the research highlights trends relevant to the 2024 regional election. The majority of candidates in 2020 were from the private sector, with a notable increase in those with bureaucratic backgrounds and a decline in legislative backgrounds. With 90.7% of candidates backed by political parties and no independent candidates for Governor or Deputy Governor, the findings point to growing bureaucratic influence and heightened financial pressures, raising concerns about conflicts of interest and corruption. As Indonesia moves towards the 2024 regional election, these insights underscore the importance of transparency and regulatory reforms to address the challenges of campaign financing. The study provides a critical foundation for policymakers and stakeholders to implement necessary reforms, ensuring a fair, transparent, and accountable electoral process.